2015
DOI: 10.1007/s11340-015-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation Into the Condition of Insulated Rail Joints by Impact Excitation

Abstract: This paper presents a feasibility study to determine if the health condition of Insulated Rail Joints (IRJs) can be assessed by examining their dynamic response to impact excitation. First, a reference dynamic behavior is defined in the frequency domain of 50-1200 Hz based on field hammer test measurements performed on a IRJ baseline (i.e., a set of IRJ without visible damage). Then, measurements on IRJs with different damage states are compared to the IRJ baseline response via the frequency response function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Consequently, the hardness of the rail top increases, as it was measured at insulated rail joints (27). The field observations of (27) showed that the hardness decreases with distance with respect to the gap. This is, less plastic deformation occurs further from the gap, and consequently, an slope develops on the rail top.…”
Section: Reference Rail Joint Analysismentioning
confidence: 84%
“…Consequently, the hardness of the rail top increases, as it was measured at insulated rail joints (27). The field observations of (27) showed that the hardness decreases with distance with respect to the gap. This is, less plastic deformation occurs further from the gap, and consequently, an slope develops on the rail top.…”
Section: Reference Rail Joint Analysismentioning
confidence: 84%
“…Then, the measured signals were transformed into the frequency domain by fast Fourier transform and the receptance function of the IRJ j,   j Rf , was calculated as follows: where f is frequency, S aF is the cross-spectrum between the force and the acceleration, and S FF the autospectrum of the force. The frequency range of the receptance function is defined by the hammers used and the applicability of the measured data, which in this case, cover frequencies between 50 and 1200 Hz [26].…”
Section: A Introduction To Hammer Test Measurementsmentioning
confidence: 99%
“…5c and d). The plastic deformation is caused by the impact occurring after the gap and has a typical wavelength of about 35-50 mm [27]. Since IRJ number 2 with light surface deformation did not have any other visible damage at the fastener and insulation layer, it will also be used for comparison in the next sections as a reference IRJ in normal condition.…”
Section: Plastic Deformation On the Rail Surfacementioning
confidence: 99%